The continuous fractional Bessel wavelet transform and its applications - Upadhyay S.K.; Mishra K.K. (My University, 2025)
In this paper, the fractional Bessel wavelet transform is introduced by exploiting the theory of the fractional Hankel transform and the boundedness of the fractional Bessel wavelet transform obtained. Time invariant linear filter associated with the fractional Hankel transform is investigated and its various properties are obtained. In the present paper, authors also expressed time-invariant linear filters in the form of the fractional Bessel wavelet transform and applications of the aforesaid filters in the integral equation are given. © 2023 Informa UK Limited, trading as Taylor & Francis Group.